Detailed investigation on the mechanism of co-deposition of different carbon nanostructures by microwave plasma CVD. (September 2016) - Kar, R.; Patel, N.N.; Chand, N.; Shilpa, R.K.; Dusane, R.O.; Patil, D.S.; Sinha, S.
Abstract: Co-deposition of carbon nanotubes (CNTs) along with nano-crystalline diamond and graphene nanowalls (GNWs) have been made possible by microwave plasma enhanced chemical vapor deposition. CNTs have been grown directly on Inconel and other nanostructures could be grown on the Si microwave attenuator placed above Inconel. The detailed mechanism involving co-deposition of sp3 and different sp2 hybridized nanostructures has been investigated through a series of experiments and windows for co-deposition have been found out. Deposited samples are characterized by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy and Raman imaging. Characterization results revealed that combination of substrate surface preparation, carbon precursor feeding rate and deposition time are the deciding factors for growth of a particular type of nanostructure. Raman spectroscopic results show that GNWs behave like nano form of turbostratic graphite and it is seen that they can be deposited even when plasma is highly perturbed. Optical emission spectroscopy results indicated that an increase in the intensity of C2 swan band increases deposition of graphitic nanostructures but decreases the required control for uniform deposition. The role of plasma sheath in co-deposition is explained with the help of a schematic model.